Acquired Hemorrhagic Diathesis of Unknown Nature - Borchgrevink, C. F; Hellem, A; Voss, D; Waaler, B. A (Thrombosis and Haemostasis, 1959)
1) A case of a severe, acquired hemorrhagic diathesis, complicating a carcinoma of the stomach, is reported.2) The only pathological hemostatic finding was a markedly prolonged bleeding time.3) Platelets were normal; the capillaries seemed to be normal. There was no increased fibrinolysis, and no other defect in his clotting mechanism could be discovered.4) The prolonged bleeding time was probably caused by a hitherto undescribed mechanism.